Dental pulp stem cells in serum-free medium for regenerative medicine. Issue 1 (2nd January 2020) - Coates, Dawn E.; Alansary, Mohammad; Friedlander, Lara; Zanicotti, Diogo G.; Duncan, Warwick J.
ABSTRACT: Mesenchymal stem cells in dentistry have multiple potential applications including alveolar ridge preservation and repair, cleft palate reconstruction, sinus grafting and ultimately pulp and dentine regeneration. The autologous application of tissue resident stem cells for regeneration is a relatively new field of research focus. Clinical application of these stem cells with multi-lineage capability requires that they be harvested and amplified in a serum- and xeno-free environment that minimises the possibility of cellular mutations and of introducing disease. The use of tissue-specific stem cells from different sites also has implications in relation to the site of harvesting and the differentiation status of the stem cells obtained. This review will examine the serum- and xeno-free culture of human dental pulp stem cells (DPSC). It will overview both the development and current practise in relation to DPSC culture and identification, to enable the future application of these cells in regenerative medicine. The phenotypic characteristics, stem-cell markers, harvesting considerations and differentiation capacity will be summarised. We will also investigate the ability of DPSCs to undergo multi-lineage differentiation in vitro and the possible clinical implications of DPSCs being derived from the neural crest.